High Figure of Merit Optical Buffering in Coupled-Slot Slab Photonic Crystal Waveguide with Ionic Liquid - Israa Abood (Nanomaterials, 2020)
Slow light with adequate low group velocity and wide bandwidth with a flat band of the zero-dispersion area were investigated. High buffering capabilities were obtained in a silicon-polymer coupled-slot slab photonic crystal waveguide (SP-CS-SPCW) with infiltrating slots by ionic liquid. A figure of merit (FoM) around 0.663 with the lowest physical bit length <semantics>Lbit</semantics> of 4.6748 µm for each stored bit in the optical communication waveband was gained by appropriately modifying the square air slot length. Posteriorly, by filling the slots with ionic liquid, the <semantics>Lbit</semantics> was enhanced to be 4.2817 μm with the highest FoM of 0.72402 in wider transmission bandwidth and ultra-high bit rate in terabit range, which may become useful for the future 6G mobile communication network. Ionic liquids have had a noticeable effect in altering the optical properties of photonic crystals. A polymer was used for the future incorporation of an electro-optic effect in buffers to realize the dynamic controlling of optical properties. Ionic liquids enhanced the transmission rate through optical materials. Additionally, the delay time in the ns-range was achieved, providing longer delay and ultra-low group velocity, which is important for light-matter interaction in light amplifiers and nonlinear devices.